Spectroscopic Properties, Magnetic Behaviours and Hirshfeld Surface Analysis of Ag[Cr(1,3-pdta)]·3H2O - Jeon, Sunghwan; Tanaka, Shinnosuke; Akitsu, Takashiro; Sang Ryo, Keon; Choi, Jong-Ha (Asian Journal of Chemistry, 2020)
The presence of various functional groups present in Ag[Cr(1,3-pdta)]·3H2O (1,3-pdta = 1,3-propanediaminetetraacetate) was confirmed by FT-IR spectral results. The electronic spectral properties and magnetic behaviours were also described. The results of our calculations yielded the crystal field splitting and Racah parameters of Dq = 1969 cm-1, B = 594 cm-1 and C = 3250 cm-1. Hirshfeld surface analysis by three-dimensional (3D) molecular surface contours and two-dimensional (2D) fingerprint plots were performed to visualize, explore and quantify the intermolecular interactions in the crystal lattice. Hirshfeld surface contours and 2D fingerprint maps revealed that the crystal packing is dominated by H···O/O···H and H···H contacts. The strong hydrogen-bonding interactions are linked with O–H···O consisting the highest fraction of 63.4% followed by these of the H···H type contributing 25.5%. Other very weak contacts of Ag···O/O···Ag, C···H/H···C, O···O, Ag···H/H···Ag and O···C/C···O are present in the title compound.